Measured thermal & daylight performance of an evacuated glazing using an outdoor test cell. (1st September 2016) - Ghosh, Aritra; Norton, Brian; Duffy, Aidan
Highlights: An experimental average overall heat transfer coefficient of 1.4 W/m 2 K was found for a vacuum glazing. Solar heat gain coefficient of a vacuum glazing was calculated from measured data. Measured interior illuminance due to vacuum glazing has been shown to the almost same as double glazing. Abstract: Outdoor characterization of thermal and daylight performance of an evacuated (vacuum) glazing has been conducted using an outdoor test cell for clear sunny day, intermittent day and overcast days. An average overall heat transfer coefficient of 1.4 W/m 2 K was found for vacuum glazing. Solar heat gain coefficient of vacuum glazing varied between 0.58 and 0.19. Vacuum glazing has potential to reduce 53% heat loss compared to a same area of double-glazing while offering nearly equal amount of heat gain. Internal daylight illuminance was found to be similar to double glazing indicating that the presence of small pillars inside vacuum glazing had no significant visual impact.